1996
DOI: 10.1038/379455a0
|View full text |Cite
|
Sign up to set email alerts
|

Two mechanisms of quantized calcium release in skeletal muscle

Abstract: Skeletal muscle uses voltage sensors in the transverse tubular membrane that are linked by protein-protein interactions to intracellular ryanodine receptors, which gate the release of calcium from the sarcoplasmic reticulum. Here we show, by using voltage-clamped single fibres and confocal imaging, that stochastic calcium-release events, visualized as Ca2+ sparks, occur in skeletal muscle and originate at the triad. Unitary triadic Ca(2+)-release events are initiated by the voltage sensor in a steeply voltage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
321
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(348 citation statements)
references
References 31 publications
24
321
2
1
Order By: Relevance
“…The marked disparity between the time course of the Ca 2ϩ rise and the duration of an action potential further strengthens the argument that most of the Ca 2ϩ rise comes from release from internal stores and not from influx via voltage-gated Ca 2ϩ channels. The time scale of 10 -15 msec is similar to that observed for amplification mechanisms in smooth muscle, cardiac muscle, and skeletal muscle (Cannell et al, 1995;Nelson et al, 1995;Klein et al, 1996). Figure 3A shows a spatial analysis of the Ca 2ϩ release sites in a surface plot of the fluorescence intensity (z-axis) along a line across the soma (x-axis) as a function of time after the field pulse ( y-axis).…”
Section: Rapid Kinetics and Spatial Analysis Of Intracellular Ca 2؉ Amentioning
confidence: 87%
See 1 more Smart Citation
“…The marked disparity between the time course of the Ca 2ϩ rise and the duration of an action potential further strengthens the argument that most of the Ca 2ϩ rise comes from release from internal stores and not from influx via voltage-gated Ca 2ϩ channels. The time scale of 10 -15 msec is similar to that observed for amplification mechanisms in smooth muscle, cardiac muscle, and skeletal muscle (Cannell et al, 1995;Nelson et al, 1995;Klein et al, 1996). Figure 3A shows a spatial analysis of the Ca 2ϩ release sites in a surface plot of the fluorescence intensity (z-axis) along a line across the soma (x-axis) as a function of time after the field pulse ( y-axis).…”
Section: Rapid Kinetics and Spatial Analysis Of Intracellular Ca 2؉ Amentioning
confidence: 87%
“…Similar volume-to-surface limitations also exist for cardiac and skeletal muscle, in which intracellular Ca 2ϩ channels are opened by Ca 2ϩ -induced ryanodine receptor opening (Cannell et al, 1995) and by an electromechanical coupling between the dihydropyridine receptor and the ryanodine receptor (Klein et al, 1996). Thus, internal somatic Ca 2ϩ amplification can be used to amplify a short action potential-induced Ca 2ϩ influx at the plasma membrane into a functionally significant Ca 2ϩ response without requiring a large density of voltage-gated Ca 2ϩ channels in the soma.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely possibility is that RyR3 are activated by the wave of Ca 2ϩ resulting from opening of RyR1 (7,34,36,37). Indeed a ''dual control'' of Ca release and an effect of RyR3 presence on the size of calcium sparks have been demonstrated (38,39). It should be noted that in RyR1-only muscles, half of the RyR1 may also be activated indirectly (9,32).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have shown that localized and spontaneous intracellular calcium release events (i.e., calcium sparks) also arise from calcium release through ryanodine receptor channels in skeletal, cardiac, and smooth muscle cells (14)(15)(16)(17)(18)(19)(20). In porcine ASM cells, earlier studies revealed occurrence of calcium sparks that were grouped and coupled across adjacent regions of the cell (16).…”
Section: Spontaneous Calcium Release Events In Airway Smooth Muscle Cmentioning
confidence: 99%